Competitividad y globalización: nuevos y viejos desafíos - Ruesga, Santos M.; Da Silva Bichara, Julimar (Papeles del Este, 2007)
This work tries to answer a question that is constantly present in both political as well as academic environments in the European community. It deals with analyzing if the problems of economic insertion in globalization which are occurring in this environment in European Union countries are due fundamentally to the effects of the growing presence in international business of countries paying low wages. For many analysts, with their consequential political interpretation, this illegitimate competition interpreted often as ”salary dumping” and by “social extension” in the economic globalized world, constitutes a threat for the future of community countries; that salaries would be based on processes of industrial deslocalization that has occurred for decades in European countries and in many other situations. The authors summarize principal economic determinants of competition on different levels: micro and macro economics as well as structural in order to concur that the competitive problems of European Members are internal, related to the characteristics of its own productive structure and to the capacity for technical as well as knowledge innovation rather than hypothetical effects of external competition by countries with low levels of wages.